2019
DOI: 10.4314/njt.v38i4.2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effects of building collapse risks on the stakeholders in the Nigerian built environment

Abstract: The study investigates the effects of building collapse risks on the stakeholders in the Nigerian built environment. Survey research design was adopted in carrying out the research and five cities in Nigeria were selected (Abuja, Ibadan, Port Harcourt, Owerri and Lagos). The target population for the study is the stakeholders in the Nigerian built environment: key professionals in the construction industry, clients/developers and users of the finished product. A sample size of 1999 was chosen using Taro Yamane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
2
2
0
Order By: Relevance
“…Overall, it is found that time overrun/extension of time has the highest likelihood of occurrence with a value of 0.677. These results echo previous studies done by Obodoh and Obodoh (2016) and Hasan et al (2014), who concluded that “Time overrun” is the top effect of delays. The second most important effect found in this study is poor quality of work due to hurrying the project, with a LI value of 0.636.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Overall, it is found that time overrun/extension of time has the highest likelihood of occurrence with a value of 0.677. These results echo previous studies done by Obodoh and Obodoh (2016) and Hasan et al (2014), who concluded that “Time overrun” is the top effect of delays. The second most important effect found in this study is poor quality of work due to hurrying the project, with a LI value of 0.636.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, it is found that time overrun/extension of time has the highest likelihood of occurrence with a value of 0.677. These results echo previous studies done by Obodoh and Obodoh (2016)…”
Section: Effects Of Delayssupporting
confidence: 93%
See 1 more Smart Citation
“…It is, however, important to note that the maintenance of buildings in Indonesia has several similarities with other countries although the methods, technology, and skills of maintenance staff are applied in different ways depending on the level of technological development and skills possessed by human resources in each country. For example, the maintenance in Nigeria, which is a developing country, is very similar to Indonesia as indicated by the corrective, preventive, and predictive types usually applied [13,42,50,51,52]. Corrective maintenance is usually implemented after a breakdown, preventive to prevent damages while predictive involves predicting the time and scale of damage [9].…”
Section: Determination Of Maintenance Prioritymentioning
confidence: 99%
“…This is seen in the use of non-professionals in construction work, the use of sub-standard materials, shoddy work, and the non-compliance and enforcement of building code specifications by clients, contractors, and regulatory bodies for selfish reasons. [4]. Therefore, in order to alleviate the frequent occurrence of collapse of concrete structures, new materials with enhanced load-bearing and weathering properties are being investigated.…”
Section: Introductionmentioning
confidence: 99%